EFFECT OF SUBLETHAL CONCENTRATIONS OF DAIRY EFFLUENT ON THE RESPIRATORY METABOLISM OF DRAGONFLY NYMPH BRACHYTAHERMIS CONTAMINATA - CHOCKALINGAM, S.; JEYACHANDRAN, K. P. S.; SHANTHY, B. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1988)
The effects of different sublethal concentrations of dairy effluent (2.5, 50, 7.5, 10.0 & 12.59. the respiratory metabolism of dragonfly nymph Brachythermis contaminata were studied oxygen consumption of nymphs was indirectly proportional to the various sublethal conce tions of the dairy effluent. Decreasing trend in oxygen consumption was also noted when duration of exposure prolonged.